P-58 Arthritic patients' views and perceptions on exercise as an adjunct treatment regime for managing their condition. (18th November 2016) - Pillay, Lervasen; Constantinou, Demitri; Coopoo, Yoganathan
Abstract : Introduction: Arthritic disease has a myriad of treatment modalities. Treatment is dependent on various types of medication stemming from the specific diagnosis. Treatment is often supplemented with dietary, lifestyle changes and exercise. Objective: This study aimed to assess the view of arthritic patients towards exercise as an adjunct treatment in managing symptoms, their knowledge of appropriate exercises, whether or not healthcare providers prescribed exercise, different healthcare providers exercise prescription habits, the exercise modes and the outcome of the effects of exercise. Methods: A cross-sectional survey study design was used. Patients presenting at two private general practitioners and a biokineticist practices in the southern suburbs of Johannesburg were invited to participate in this questionnaire-based study. Patients that met the inclusion criteria (any arthritic disease with or without a co-morbid disease not contra-indicating exercise) were included in the study. Questions were developed to determine various aspects of the effect of exercise and participants' attitudes toward exercise as an additional management tool in arthritic patients. These were all self-reported by the participant using the questionnaire. In addition, information on the type of healthcare providers prescribing exercise, exercise modes and outcomes of exercise were also gathered. Outcomes (improvements in participants' condition, symptoms and activities of daily living with exercise) were used as criteria for improvement. Results: A total of 67 participants were surveyed - 25% male and 73% female. Two percent were unspecified. Age distribution: 60% > 50 years old, 36% were 30-50 years old and four percent < 30 years of age. Most suffered from osteoarthritis (N = 29), rheumatoid arthritis (N = 27), gout (N=five) and post traumatic arthritis (N=three). The remaining participants were not specific. Exercise was advised mostly by doctors, followed by physiotherapists then biokineticists. Exercise that was advised by doctors was general (no specifics regarding intensity and time). It mostly included walking (48%).%. Pain was measured using a numeric pain scale and activities of daily living were self-reported by the participants using the questionnaire. Exercise alone diminished pain (p = 0.18) and improved activities of daily living by 11%, while medication alone did relieve pain (p = 0.034) and improved activities of daily living by 21%. The largest improvement and statistically significant finding in perceived pain relief was with both exercise and medication (p = 0.01) with a 32% improvement in activities of daily living. Participants surveyed are of the view that exercise assists them in managing the symptoms of arthritis. Conclusions: Exercise is an important adjunctive treatment modality. Doctor's advice was very non-specific. Participants believe that exercise can benefit them. This study's findings suggest that healthcare providers need to prescribe exercise more specific to the patient's condition and physical capabilities. Observations and analysis from the study concludes that medical treatment aided by exercise will improve symptoms in patients with arthritic disease. There is no "one size fits all" exercise prescription. Future research should be directed toward exploring further these findings and the reasons why healthcare practitioners fail to be specific in their exercise advice.